The frequency and severity of epistaxis in children with sickle cell anaemia in eastern Uganda: a case-control study - Nardo-Marino, A; Williams, TN; Olupot-Olupot, P (BioMed Central, 2017)
Background There are a paucity of data on epistaxis as it pertains to sickle cell anaemia. Some case studies suggest epistaxis to be a significant complication in patients with sickle cell anaemia in sub-Saharan Africa; however, no robust studies have sought to establish the epidemiology or pathophysiology of this phenomenon.